Cancellation of streak artifacts in radial abdominal imaging using interference null space projection. Issue 3 (24th May 2022) - Fu, Zhiyang; Johnson, Kevin; Altbach, Maria I.; Bilgin, Ali
Abstract : Purpose: In radial abdominal imaging, it has been commonly observed that signal from the arms cause streaks due to system imperfections. We previously introduced a streak removal technique (B‐STAR), which is inherently spatially variant and limited to work in image space. In this work, we propose a spatially invariant streak cancellation technique (CACTUS), which can be applied in either image space or k‐space and is compatible with iterative reconstructions. Theory and Methods: Streak sources are typically spatially localized and can be represented using a low‐dimensional subspace. CACTUS identifies the streak subspace by leveraging the spatial redundancy of receiver coils and projects the data onto the streak null space to eliminate the streaks. When applied in k‐space, CACTUS can be combined with iterative reconstructions. CACTUS was tested in phantoms and in vivo abdominal imaging using a radial turbo spin‐echo pulse sequence. Results: In phantoms, CACTUS improved T2 estimation in comparison to previous de‐streaking methods. In vivo experiments showed that CACTUS reduced streaks and yielded T2 estimation, in regions affected by streaks, closer to a streak‐free reference. Evaluation using a clinical abdominal dataset ( n = 20) showed that CACTUS is comparable to B‐STAR and yields significantly better signal preservation and streak cancellation than coil removal and suppression methods. Conclusion: CACTUS provides superior signal preservation and streak reduction performance compared to coil removal and suppression methods. As a clear advantage over B‐STAR, CACTUS can be integrated with iterative reconstruction methods. In abdominal T2 mapping, CACTUS improves the accuracy of parameter estimation in areas affected by streaks.